Akronim Bahasa Tabu BH Perspektif Pendidikan Islam - Moh. Sakir; Robingun Suyud El Syam; Salis Irvan Fuadi (Jurnal Riset Rumpun Agama dan Filsafat, 2023)
This research focuses on the research objective of uncovering the taboo language acronym BH from the perspective of Islamic education, by tracing the background of the language, then focusing on how new meanings are generated where specific searches have not revealed them. This article uses a qualitative approach to describe, analyze, and interpret forms of taboo language with an emphasis on analyzing the context. The results of the study found that BH is an acronym by shortening it in the form of a combination of letters with a euphemism approach, namely the use of expressions to soften words to replace taboo language so as to produce a new word. The function of the new word is intended to soften the word so that the taboo element does not become dominant. Refining words in order to avoid harsh taboos is in accordance with the essence of Islamic education, where a Muslim is ordered to say good things, and avoid dirty and harsh words. The implications of research on the need to refine taboo essence requires more specific research. Research contributes to Islamic education regarding strategies to avoid taboo languages.